Evaluation of Crestal Bone Resorption around Dental Implants in Flapped and Flapless Surgical Techniques Depending on Cone Beam CT Scan (Comparative Study) - Mustafa A Al Najjar; Sahar Sh Al Adili (College of Dentistry/ University of Baghdad, 2019)
Background: The long term survival of dental implants is evaluated by the amount of crestal bone loss around the implants. Some initial loss of bone around dental implants is generally expected. There is reason to believe that reflecting a mucoperiosteal flap promotes crestal bone loss in the initial phase after an implant has been inserted. The surgical placement of a dental implant fixture is constantly changing and in recent years, there has been some interest in developing techniques that minimize the invasive nature of the procedure, with flapless implant surgery being advocated. The purpose of this study was to compare the radiographic level of the peri- implant bone after implant placement between traditional flapped surgery and flapless approach depending on CBCT during 24 weeks healing period. Materials and Methods: A total of 25 Iraqi patients with an age ranged of 20-60 years who received 46 implants. Were randomized into two groups: control group which involved 27 implants inserted by conventional flapped surgical approach and study group which involved 19 implants inserted by flapless surgical approach. The bone level was measured by CBCT for each implant at buccal and palata/lingual sides at two times, immediately after implant placement (base line data), and after 24 weeks healing period. Results: There was no significant difference between study (flapless) and control (flapped) groups in the mean of total crestal bone resorption for buccal and palatal side after 24 weeks from implant placement (P= 0.393 for buccal side and P= 0.214 for palatal side). There was highly significant difference between buccal and palatal side regarding crestal bone loss around implants (P = 0.001) Conclusions: Bone resoption around dental implants placed with conventional flap surgery compared to flapless surgery does not seem to be influenced during the healing period before implant loading.